Peranan Sekuen Susceptibility Weight Imaging (SWI) Pada Pemeriksaan MRI Brain Pada Kasus Tumor - Zefanya G. Pandelaki; Mohammad Agus Pribowo; Ni Putu Rita Jeniyanthi (Pusat Riset dan Inovasi Nasional, 2024)
The aim of the research is to find out the role of the transverse suspectibility weighted imaging (SWI) sequence in brain MRI examination techniques in tumor cases. The research method used in this research is a qualitative descriptive study that uses a literature study approach to explore, analyze and identify information about how the Susceptibility Weighted Imaging (SWI) sequence plays a role in the Brain MRI examination process in patients who have tumors. The results and discussion of the literature review show: 1) Susceptibility-Weighted Imaging (SWI) on MRI brain has an important role in detecting blood degradation products, calcification and iron accumulation in glioblastoma. SWI allows visualization of small blood vessels, detection of iron, as well as identification of areas of calcification within the tumor, providing a more detailed picture of the nature and malignancy of glioblastoma. The Intratumoral Susceptibility Signal (ITSS) on SWI images is a visual marker associated with microhemorrhage, neoangiogenesis, and calcification, enabling tumor grading based on the frequency and distribution of these signals. In addition, Intralesional Susceptibility Signal (ILSS) also has an important role in differentiating glioblastoma from abscesses and metastases, with high levels of ILSS tending to be associated with tumor severity. Thus, the integration of SWI and ITSS and ILSS analysis can make a significant contribution to the characterization and assessment of the level of malignancy. 2) Susceptibility-Weighted Imaging (SWI) in the diagnosis of glioblastoma has the advantage of providing internal visualization of the tumor with high resolution. SWI is highly sensitive to differences in tissue susceptibility, allows the detection of neovascularization, hemorrhage, and calcification within glioblastoma, and provides detailed information about cerebral vascular anatomy. The advantages of SWI include its ability to image the Intratumoral Susceptibility Signal (ITSS) and Intralesional Susceptibility Signal (ILSS) and increase the visibility of low signal intensity structures. However, its shortcomings, namely sensitivity to artifacts, dependence on susceptibility phenomena, and subjective interpretation are aspects that need to be considered.